Perilaku Toxic Dalam Permainan Online Mobile Legends Bang Bang - Maulana Abdul Arifin; Linggua Sanjaya Usop; Patrisia Cuesdeyeni; Rini Susilawati; Suryanata Suryanata; Umega Umega (Universitas Palan, 2023)
This research was carried out against the background of player behavior in the Mobile Legends Bang Bang game, in the Mobile Legends Bang Bang game Toxic behavior often occurs in the Mobile Legends Bang Bang Online Game, where this behavior often occurs when in a team there is a player who plays very aggressively. bad, doing feeders, differences in countries, differences in ethnicity, even differences in religion and so on. This research aims to find out (1) How toxic behavior takes the form of sarcasm in the online game Mobile Legends Bang Bang, (2) How toxic behavior takes the form of cynicism in the online game Mobile Legends Bang Bang. This research is field research and uses a qualitative approach. The research location is the barracks/boarding house where you live. Data sources in this research include data on the research location and data regarding mobile legends from players and barrack/boarding house owners. Secondary data consists of data from the online game Mobile Legends and toxic behavior obtained from other sources. The data collection technique used is through observation and documentation. For technical data analysis using data reduction, data presentation and drawing conclusions. Toxic in the form of sarcasm is a rude insult intended to hurt other people in the Mobile Legends game. The team is annoyed at players who are considered bad and burden the team. Toxic cynicism criticizes in a frank language style that fits the facts. Cynicism or excessive skepticism is a condescending attitude that is detrimental and hurts the feelings of others. It involves negative or cynical judgments of other people, ideas, or situations with the aim of ridiculing or feeling better than the other person. This text will be shortened to a few sentences or important points, while maintaining the essence of the information conveyed.